Armenia's transformative urban future national urban assessmentt. (Annual Reports of the Asian Development Bank-Japan Scholarship Program., 2019)
The program gives qualified citizens from developing member countries of the Asian Development Bank an opportunity to take postgraduate studies in economics, business and management, science and technology, and other development related fields at 29 educational institutions in Asia and the Pacific. Between 1988 and 2018, Japan contributed 182 million to the program. An average of 139 scholarships are awarded each year.